2019
DOI: 10.4081/pr.2019.8248
|View full text |Cite
|
Sign up to set email alerts
|

Serological Profile of Hepatitis B in Children after the Introduction of Its Vaccination in Burkina Faso

Abstract: Viral hepatitis B is a public health issue. We establish the children serological profile of hepatitis B in Bobo-Dioulasso, six years after the introduction of hepatitis B vaccine into the Expanded Program on Immunization. This was a descriptive study of prospective data collection carried out in the Department of Pediatrics and the laboratory of virology of the Centre MURAZ of Bobo-Dioulasso between March 2013 and May 2013. Blood samples were made in search of the following hepatitis B serological markers: an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…Peak anti-HBs concentration achieved after primary vaccination and age-dependent decay in anti-HBs titers play key roles in protection against infection [16]. Breakthrough infection rates stood at 2.3% in our study population, mimicking findings from Ghana and Burkina Faso [19,20].…”
Section: Discussionsupporting
confidence: 69%
“…Peak anti-HBs concentration achieved after primary vaccination and age-dependent decay in anti-HBs titers play key roles in protection against infection [16]. Breakthrough infection rates stood at 2.3% in our study population, mimicking findings from Ghana and Burkina Faso [19,20].…”
Section: Discussionsupporting
confidence: 69%
“…10 Children born to HBV-infected mothers often become chronic carriers of HBV surface antigen (HBsAg). 11 13 In West Africa, hepatitis B is a main contributor to cirrhosis and liver cancer, with about 2 million disability-adjusted life-years attributable to viral hepatitis. 14 However, a low proportion of HBV-infected people, estimated to be 0.3% in 2015, has been diagnosed in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the studies varied between countries, as well as within the same country. Studies showed that protective levels of HbsAb antibodies decrease with age after vaccine introduction [30,43]; however, most of the studies included in this review did not report prevalence by age group.…”
Section: Limitationsmentioning
confidence: 93%